DEVELOPMENT OF EVALUATION BASED WORDWALL MEDIA TO IMPROVE ARABIC LANGUAGE LEARNING OF SENIOR HIGH SCHOOL - M. Zunaidul Muhaimin; Nunik Zuhriyah (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2024)
Learning evaluation is a measure of success in education in this era, this study aims to develop an Arabic learning evaluation media based on educational games in helping the smooth learning process and determine the feasibility of Arabic learning evaluation media through wordwall educational games from expert validator assessments. This research method uses Research and Development with qualitative and quantitative approaches. The theory used in this research is the ADDIE model theory which consists of 5 stages is the Analyze, Design, development, implementation and evaluation. The research object is students of the 10th grade in Nurul Huda Surabaya. Data collection techniques in this study were observation, interview, documentation and test techniques. The assessment results from media expert validation get a percentage of 90% with a very feasible category. In the validation of material experts, the development of evaluation media gets a percentage of 84% with a very feasible category. Furthermore, the assessment of the students' response received a percentage of 86% with a very feasible category. So it can be concluded that the evaluation media for learning Arabic through wordwall educational games is feasible to use.